2020
DOI: 10.3389/fpsyg.2020.01435
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Traumatic Stress in Italian Police Officers: The Role of Job Demands and Job Resources

Abstract: Police officers are among the workers most exposed to acute or chronic stressful events, which compromises their psychosocial well-being and physical health. Exposure to traumatic events, human suffering, problematic situations and episodes of violence can cause psychological damage and lead to the development of secondary traumatic stress. The aim of this research is to explore the effect of job demands and job resources on secondary traumatic stress in police officers. To better understand this phenomenon an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…This might be the result of potential cognitive decline connected with aging, which gradually decreases the ability to process traumatic events (Foa and Kozak 1986). Length of service also seems to increase the odds of developing symptoms of post-traumatic stress disorder, which might be the result of high demands and low resources in the workplace and burnout (Acquadro Maran et al 2020;Foley and Massey 2020). In the case of number of types of traumatic events, the more diversified the traumatogenic stimuli, the higher are the odds of developing PTSD symptomatology (similar results were found by Hartley et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…This might be the result of potential cognitive decline connected with aging, which gradually decreases the ability to process traumatic events (Foa and Kozak 1986). Length of service also seems to increase the odds of developing symptoms of post-traumatic stress disorder, which might be the result of high demands and low resources in the workplace and burnout (Acquadro Maran et al 2020;Foley and Massey 2020). In the case of number of types of traumatic events, the more diversified the traumatogenic stimuli, the higher are the odds of developing PTSD symptomatology (similar results were found by Hartley et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, numerous studies have revealed that police officers face both physical and psychological health problems, which may affect police officers’ work quality (e.g. decision-making or the ability to react quickly to dangerous situations), personal relationships and quality of life (Acquadro et al 2020 ; Demou et al 2020 ; Violanti et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Police officers face both chronic and acute stressors at work. The observation of traumatic events, human suffering and episodes of violence can lead to secondary traumatic stress (Acquadro et al 2020 ). Depression, anxiety disorders, cardiovascular disease at a younger age, alcoholism, occupational burnout, post-traumatic stress disorder, or even the risk of suicide are more common among police officers than other professionals (Queiros et al 2020 ; Acquadro et al 2020 ; Demou et al 2020 ; Ivleva and Pajarskienė, 2019 ; Purba and Demou 2019 ; Violanti et al 2017 ; Wagner et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Police organizations, particularly border police, are public service entities rated as highly stressful with a high level of daily ( Siu et al, 2015 ; Wolf, 2017 ; Demou et al, 2020 ; Lentz et al, 2020 ) and uncontrollable risk ( Cartwright and Roach, 2021 ; Chitra and Karunanidhi, 2021 ; Jackman et al, 2020 ; Papazoglou et al, 2020b ), which face numerous situations, such as humanitarian crises at borders, that have the capacity to generate conflict and role ambiguity for their members ( Antón, 2009 ; Acquadro Maran et al, 2020 ; Queirós et al, 2020 ). In these organizations, high cooperation is required ( Rexeis, 2017 ), there is a strong hierarchy, and often an authoritarian leadership style ( Piotrowski et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%